Spurring Innovation-Led Growth in Argentina : Performance, Policy Response, and the Future - Gurcanlar, Tugba; Criscuolo, Alberto; Gomez Gaviria, Daniel; Cirera, Xavier (Washington, DC: World Bank, 2021)
A new, innovation-led growth model would enable Argentina to increase economic stability and achieve stronger shared prosperity. Argentina can escape boom-and-bust cycles and accelerate its recovery from the COVID-19 pandemic with an innovation-driven economy that, in addition to factor accumulation, fuels higher productivity growth across all its sectors. Such a growth model should build on Argentina’s strengths in human capital, research, and firm-level capabilities, which would help diversify the economy and make it more inclusive and less susceptible to external shocks, providing the country with a stronger buffer at times of uncertainty. Despite the volatility of the past few decades, Argentina has been able to develop important pockets of success in high-end research and in frontier productive sectors such as biotechnology and knowledge economy. All of these should be better exploited and strengthened through public-private partnerships, targeted investments, and an enabling business environment to increase innovation’s contribution to economic growth. A resilient economic recovery will, in part, require a long-term vision and a policy framework that builds a sustainable national innovation system. To contribute to the strengthening of such a national innovation system, this report reviews holistically the innovation performance in Argentina, identifies some of the main gaps and strengths, and discusses appropriate policy responses. The report also examines regional differences in innovation performance and reviews the policy effectiveness of recent initiatives that have focused on industry and science linkages and knowledge-based entrepreneurship. The lessons from these impact evaluations and findings of the comparative evaluation of Argentina’s innovation landscape are intended to provide guidance in the design and strengthening of existing and future innovation policies in Argentina.